The Use Of Sadd Al-Dhari'ah Incontemporary Islamic Family Law In Indonesia: Concept And Practice - Fajar Rachmadhani; Muchammad Ichsan; Mualimin Mochammad Sahid (USIM PRESS, 2024)
Malaysian Journal of Syariah and Law (MJSL) Volume 12 Issue 1 Page (206-215)